Analisis Keterampilan Dasar Mengajar Mahasiswa Kependidikan dan Nonkependidikan Peserta Program Kampus Mengajar - Connery B, Irene Jane; Zahra, Puji Febrian; Lolita, Ristiani; Sofyan, Sofyan; Pratama, Robin (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze and describe the implementation of the Teaching Campus Program with a focus on the basic teaching skills possessed by education and non-education students in Jambi City. The research subjects consisted of 4 students from education and non-education study fields who are students of the Teaching Campus Program in Jambi City placed in junior high schools. The analysis techniques used were data reduction, data presentation, and finally conclusion drawing. Furthermore, triangulation was used to test the validity of the research data. The results of the study indicate that in the implementation of the Teaching Campus Program, especially teaching practice, students require basic teaching skills. Then, it was found that there were differences in abilities between education and non-education students which occurred due to the lack of training in basic teaching skills and knowledge related to pedagogical learning and microteaching. Furthermore, obstacles experienced by education students during the program were the lack of school infrastructure that hindered students in developing learning variations, different obstacles experienced by non-education students who had obstacles in teaching practice and conversion.